Archive value: measuring the palaeo-information content of peatlands in a conservation and compensation perspective. Issue 1 (1st January 2018) - Greiser, Caroline; Joosten, Hans
ABSTRACT: The value of peatlands as archives for vegetation, landscape, climate, and human history is well known, but often neglected in conservation planning. Archive value is the potential to satisfy future (yet unknown) demands for information about the past. This study aims at assessing the comparative archive value of a set of peatlands, to identify the most similar alternatives for three peatlands and to estimate the archive loss in case of their destruction. Representative cores from 49 peatlands in the region were assessed with respect to age, depth, resolution, (in)completeness, evenness, and diversity of substrates, peat accumulation status, and thickness of every single substrate type. After using cluster analysis to identify archive types and the relatedness among peatlands, the archive value of each peatland was expressed as a proportion of the total regional archive. We found candidates for compensating the three threatened peatlands, but also identified other archives of high conservation interest according to our criteria. The outcomes appeared rather robust but were determined by the criteria, resolution, and algorithms chosen. This work presents a first step towards developing an objective and consistent evaluation procedure of peatland archives, allowing the archive value to be considered in conservation and management decisions. EDITED BY Graciela Rusch